(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The aim of this article is to present a questioning of the notion of ambiguity as a recurring position of anthropologists, parting from the comparison of two similar experiences of grief and family loss, one at the field and one at a personal level, which entailed the reconsideration of the ways the social group reinforces the experience of loss, and how at the same time this experience supposes a reassessment of the role of the researcher that involves assuming that we’re always situated at the field.